Theoretical foundations in support of small and medium towns - De Noronha, Maria Teresa (2020)
This theoretical review aims to create a comprehensive and systematic analysis based on previously published literature explaining how contemporary technological developments may promote new paths for small and medium-sized towns (SMTs) and their networking systems. Much has been said concerning the capacity of towns to absorb strategic knowledge, which is highly dependent on local governance systems. In this paper, five levels of multidisciplinary approaches will be addressed so as to pinpoint the theoretical grounds for the promotion and advocacy of small and medium-sized towns (SMTs) as major drivers of regional sustainability: agglomeration advantages and networking efficiencies-representing strict economic accounting of cost and benefits; clustering in a context of online environments, and its extension to open networking systems; sustainable innovation processes for SMTs, technology, and knowledge transfer in open innovation systems-both settings for discussions within the framing of new technological developments and artificial intelligence; knowledge and new technological developments with local spillovers-to be enhanced employing new educational programs and learning diffusion at advanced levels; the social functions of small and medium-sized towns-to be addressed in the areas of sociology, architecture, and planning.